Sucrose synthase dynamics and its potential role in heat stress tolerance in cereals - Parihar, Priyanka; Jaiswal, Jai Prakash; Verma, Ashok Kumar; Kumar, Amit (Frontiers in Plant Science, 2025)
Sucrose synthase (SuSy) is a key enzyme in plant carbohydrate metabolism, catalyzing the reversible conversion of sucrose into UDP-glucose and fructose. SuSy is central to several developmental and metabolic processes, where its activity is closely linked to biomass accumulation, pollen viability, grain filling, and seed development. This review explores the role of SuSy, in comparison with invertase, examines its enzymatic interactions, and highlights its contribution to metabolic adaptation under heat stress, while emphasizing its critical role in strengthening sink capacity. Elevated temperatures negatively impact sucrose metabolism and source–sink relationships, disrupting yield formation in cereal crops. SuSy, with its distinct isoforms and subcellular localizations, adapts flexibly to thermal stress, maintaining sucrose flux and stabilizing energy supply in developing tissues. Its stress-responsive expression patterns suggest that specific isoforms could be targeted to enhance thermotolerance. Overall, understanding the spatial, temporal, and regulatory dynamics of SuSy offers promising avenues for developing climate-resilient crops. Harnessing its full potential through targeted breeding and gene editing could be pivotal in mitigating the adverse effects of rising temperatures on global food security.